Malay Pantun: A Study of its Exquisiteness and Exclusivity in the Society (Malay Literature, 2023)
Pantun is the treasure house of thoughts, poetry and the life of the Malays. In every phase of life, people convey pantun in their own style in order to represent the said phase. Hence, this paper highlights exquisiteness and exclusivity of pantun in the Malay society. This paper also examines the uniqueness of children's pantun, this paper attempt to study the beauty of children's pantun by tracing them from all phases of childhood, from their arrival as babies, their lives in the cradle (often with the vocal accompaniment of their mother, sister or grandmother, singing playful pantun), and continued right through their early childhood and also instilled through games. In this phase, the pantun are more serious with a more thoughtful intention of instilling what the society considers to be proper behaviour, courtesy and civility. Almost all lessons in pantun are enclosed within two or four lines, and ab-ab rhymes, and is considered to be the best medium that is offered in the language. While the children remember the words in the pantun, they also remember the lessons and messages contained within. Pantun also provide a background or metaphors of what young people go through in life. As children grow, the lessons become weightier in nature as the meanings become clearer. In addition, as their emotions develop, the pantun accompany the young men and women more romantically, for which its function is most famous in this phase. These are the main phases of life, and the pantun is a favourable medium that renders its space to all of them.Full text: PDF